2012
DOI: 10.1007/s00244-012-9750-y
|View full text |Cite
|
Sign up to set email alerts
|

Decabromobiphenyl, Polybrominated Diphenyl Ethers, and Brominated Phenolic Compounds in Serum of Cats Diagnosed With the Endocrine Disease Feline Hyperthyroidism

Abstract: The incidence of cats being diagnosed with feline hyperthyroidism (FH) has increased greatly since it was first described in 1979. The cause of FH has not been established. Hypothetically, there is a link between increasing FH and exposure to brominated flame retardants. Much greater polybrominated diphenyl ethers (PBDE) concentrations have been reported in cat serum compared with human serum, likely due to cat licking behaviour. This study aimed to extend the present identification of brominated compounds in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 25 publications
0
34
1
Order By: Relevance
“…The PBDEs levels in dog serum were 30% lower in present study than those earlier reported in US dogs (Environmental Working Group, EWG, 2008;Venier and Hites, 2011). Indoor dust ingestion accounts up to 90% of the total daily intake of PBDEs in toddlers, whose rug crawling and hand-to-mouth behavior resembles with walking and grooming of cats (Mercier et al, 2011;Norrgran et al, 2012). Furthermore, indoor dust ingestion was suggested as the dominant source for PBDEs exposure to cats in US (Guo et al, 2012).…”
Section: Comparison Of Levels Of Ohcs In Pet Serum From Pakistan Withcontrasting
confidence: 75%
See 1 more Smart Citation
“…The PBDEs levels in dog serum were 30% lower in present study than those earlier reported in US dogs (Environmental Working Group, EWG, 2008;Venier and Hites, 2011). Indoor dust ingestion accounts up to 90% of the total daily intake of PBDEs in toddlers, whose rug crawling and hand-to-mouth behavior resembles with walking and grooming of cats (Mercier et al, 2011;Norrgran et al, 2012). Furthermore, indoor dust ingestion was suggested as the dominant source for PBDEs exposure to cats in US (Guo et al, 2012).…”
Section: Comparison Of Levels Of Ohcs In Pet Serum From Pakistan Withcontrasting
confidence: 75%
“…However, the concentration of other major OHCs, except OCPs, were significantly higher (p b 0.05) in cat serum compared to children serum. The higher concentrations of OHCs, specifically of PBDEs, in cat serum may be due to the intake of dust bound chemicals from their licking on the various materials and crawling on the floor behavior (Mercier et al, 2011;Norrgran et al, 2012), which is more closely matched with toddlers (aged between 1 and 3 years), but not with young children (aged between 5 and 10 years) as available from Ali et al (submitted for publication). Another possible explanation of higher OHCs in cats might be the fact that cats have a limited ability to metabolize xenobiotics via glucuronidation (Court and Greenblatt, 1997).…”
Section: Are Pets Suitable Sentinels For Humans?mentioning
confidence: 87%
“…BB-209 was not detected in human samples; it was detected in one of the pooled cat sera in Sweden at 450 ng g –1 lw in one pooled sample, thus highly limiting comparability to our study. 45 …”
Section: Discussionmentioning
confidence: 99%
“…For example, the polyphenolic compound bisphenol A, which is used as a plasticizer in can linings, has been detected in canned cat food and may act as a thyroid disruptor (Edinboro et al 2004, Schecter et al 2010. In a similar vein, recent studies both in the USA and Sweden have reported high levels of polybrominated diphenyl ethers (PBDEs) in cats, a fire-retardant with known thyroid-disrupting properties (Dye et al 2007, Guo et al 2012, Mensching et al 2012, Norrgran et al 2012. As PBDEs migrate out of the flame-protected materials (e.g.…”
Section: Why Has Feline Nodular Goiter Reached Such Epidemic Proportimentioning
confidence: 99%